Relationships between internal training intensity and well-being changes in youth football players - Silva, Rui Miguel (2022)
The aim of this study was two-fold: (i) to analyze the variations of training intensity and well-being measures of youth football player over a 38 week period; and (ii) to test the relationships between training intensity and well-being variations throughout a youth football season. This study followed a longitudinal design, lasting 38 weeks. Twenty-five players (age: 15.0 ± 0.4 years) participated in this study. Participants were monitored daily to quantify the training intensity (TI) using the session-rate of perceived exertion (s-RPE) and its related indices: training monotony (TM), weekly training intensity (wTI), mean training intensity (mTI), and 5-day average (5d-AVG). A four-item questionnaire was collected daily to quantify the well-being status of each player. Fatigue, stress, delayed onset muscle soreness (DOMS), sleep quality, and the Hooper Index (HI) measures were analyzed. Kruskal-Wallis H test revealed significant differences for TM, mTI, wTI and 5d-AVG (H = 359.53, p = 0.001, η2 = 0.35; H = 414.97, p = 0.001, η2 = 0.41, H = 258.42, p = 0.001, η2 = 0.24 and H = 282.18, p = 0.001, η2 = 0.26). A positive large correlation was found between TM and sleep quality (r = 0.65, p = 0.05) and a negative large correlation between mTI and sleep quality (r = −0.69, p = 0.04). In conclusion, both TI and well-being measures present significant between-week differences at different periods of the season. Also, the variations of sleep quality seem to depend on TM and mTI variations across a youth football season.